Spin-polarized hot electron injection into two-dimensional electron gas by magnetic tunnel transistor - Tae, Gikoan; Eom, Jonghwa; Song, Jindong; Kim, Kwangyoun (JAPAN SOC APPLIED PHYSICS, 2007)
A magnetic tunnel transistor has been fabricated on top of a modulation-doped GaAs/AlGaAs heterostructure that provides a high-mobility two-dimensional electron gas. The emitter and base of the magnetic tunnel transistor consisted of a ferromagnetic metal, whereas the collector consisted of the two-dimensional electron gas. Spin polarized hot electrons from the emitter were filtered by the CoFe base layer and then injected into the collector, leading to a finite magnetocurrent ratio. The magnetocurrent ratio decreased as the hot electron energy was increased by increasing the bias voltage between the emitter and the base above a certain threshold voltage. We observed magnetocurrent ratios of similar to 27% at 17 K and similar to 2% at 300 K, indicating that spin-polarized hot electrons are injected into the two-dimensional electron gas from 17 K up to room temperature.
Keywords: ROOM-TEMPERATURE; MAGNETOCURRENT